Öğrenilen Namus Algısı Perspektifinde Kadın Cinayetleri: Muş İli Örneği - Ateş, Sultan (Muş Alparslan Üniversitesi, 2020)
The concept of honor, which has a very important place in gender studies, is also subjected to gender-based discrimination in our country too. When considered from this perspective, honor refers to a phenomenon that is implanted on the female body and needs to be controlled by women's movements. The concept of honor, which is not directly associated with men, indirectly affects the man who thinks he has a woman., the effects of the learned perception of honor in femicides in the province of Muş, which are analyzed on the axis of honor, were examined. As a result of the study, it is seen that the concept of honor, which is reduced to the woman's body and sexual purity, has an important effect on murders. It is possible to see the social structure of Muş, the meaning attributed to the concept of honor here, the way of learning honor, the fact that passion is woman-centered, and the reason why men use the concept of honor in this examination, where primary sources are used with the indictments obtained from the Muş Courthouse.

Toplumsal cinsiyet çalışmalarında çok önemli bir yere sahip olan namus kavramı; Türkiye’de de cinsiyet temelli bir ayrıma tabi tutulmaktadır. Namus bu çerçeveden bakıldığında kadın için, kadın bedenine nakşedilen ve kadının hareketleri ile kontrol edilmesi gereken bir olguya işaret etmektedir. Erkek ile doğrudan ilişkilendirilmeyen namus kavramı ise kadına sahip olduğunu düşünen erkeği dolaylı yoldan etkilemektedir. Muş ilinde gerçekleşen ve namus ekseninde incelenen kadın cinayetlerinde, öğrenilen namus algısının etkileri irdelenmiştir. Çalışma sonucunda kadının bedenine ve cinsel saflığına indirgenen namus kavramının cinayetler üzerinde önemli bir etkiye sahip olduğu görülmektedir. Muş Adliyesi’nden elde edilen iddianamelerle birincil elden kaynakların kullanıldığı bu incelemede, Muş’un toplumsal yapısını, burada namus kavramına atfedilen anlamı, namusun öğrenilme biçimini, tutkunun kadın merkezli oluşunu ve erkeğin namus kavramını kullanış gerekçesini görmek mümkündür.
Femicide in the Perspective of Learned Perception of Honor: the Case of Muş
anemon
Keywords: Femicides; Honor; Learned Honer; Violence; Gender; kadın cinayetleri; namus; öğrenilen namus; şiddet; toplumsal cinsiyet